Hubungan Kematangan Karir dengan Psychological Well-being pada Fresh Graduate di Kota Bandung - Syafirah Mutiara Hakim; Andhita Nurul Khasanah (Bandung Conference Series: Psychology Science, 2022)
Abstract. One of the developmental tasks of emerging adulthood is to explore identity in the workplace. Same as the task of fresh graduates to find their work identity. On the other hand, fresh graduates experience feelings of anxiety due to the increasing number of unemployment and job competition, are unable to establish a settled personal identity, and tend not to want to discuss development tasks they have to deal with. These concerns illustrate that most of them are not ready to face the world of work, which in Super's definition (1977) is said to be a low level of career maturity. Failure to develop a career identity has been found in several studies to be associated with psychological well-being . The purpose of this study was to determine the relationship between career maturity and psychological well-being on fresh graduates in Bandung City. The method used is a correlational design with a quantitative approach with the number of participants as many as 200 people. The measuring instrument used aspects of Super career maturity by Dewi Sartika (2003) which was tried out again and Ryff's Psychological Well-being Scale using the Spearman Rank correlation test analysis technique. The results of the analysis show a positive relationship between career maturity and psychological well-being on fresh graduates in Bandung City (rs = 0.728), meaning that the higher the career maturity on fresh graduates, the higher their psychological well-being. Abstrak. Salah satu tugas perkembangan emerging adulthood adalah mengeksplorasi identitas di bidang pekerjaan. Hal tersebut sejalan dengan tugas fresh graduate untuk mencari identitas kerjanya. Disisi lain, fresh graduate mengalami perasaan cemas akibat meningkatnya jumlah pengangguran dan persaingan lapangan kerja, tidak mampu menetapkan identitas pribadi yang settle, dan cenderung untuk tidak ingin membahas tugas perkembangan yang harus dihadapinya. Kekhawatiran-kekhawatiran tersebut menggambarkan bahwa sebagian besar dari mereka memang belum siap untuk menghadapi dunia kerja, dimana dalam pengertian Super (1977) kekhawatiran tersebut dikatakan sebagai tingkat kematangan karir yang rendah. Kegagalan untuk mengembangkan identitas karir telah ditemukan dalam beberapa penelitian mengindikasikan psychological well-being individu yang rendah. Tujuan penelitian ini untuk mengetahui seberapa erat hubungan kematangan karir dengan psychological well-being pada fresh graduate di Kota Bandung. Metode yang digunakan adalah desain korelasional dengan pendekatan kuantitatif dengan jumlah partisipan sebanyak 200 orang. Alat ukur yang digunakan adalah penurunan aspek-aspek kematangan karir Super oleh Dewi Sartika (2003) yang di try out ulang dan Ryff’s Psychological Well-being Scale dengan menggunakan teknik analisis uji korelasi Rank Spearman. Hasil analisis menunjukkan hubungan yang positif antara kematangan karir dengan psychological well-being pada fresh graduate di Kota Bandung (rs = 0.728), artinya semakin tinggi kematangan karir fresh graduate semakin tinggi psychological well-being-nya.